-5(3w+2)+4w=6w/2

Simple and best practice solution for -5(3w+2)+4w=6w/2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(3w+2)+4w=6w/2 equation:



-5(3w+2)+4w=6w/2
We move all terms to the left:
-5(3w+2)+4w-(6w/2)=0
We add all the numbers together, and all the variables
-5(3w+2)+4w-(+6w/2)=0
We add all the numbers together, and all the variables
4w-5(3w+2)-(+6w/2)=0
We multiply parentheses
4w-15w-(+6w/2)-10=0
We get rid of parentheses
4w-15w-6w/2-10=0
We multiply all the terms by the denominator
4w*2-15w*2-6w-10*2=0
We add all the numbers together, and all the variables
-6w+4w*2-15w*2-20=0
Wy multiply elements
-6w+8w-30w-20=0
We add all the numbers together, and all the variables
-28w-20=0
We move all terms containing w to the left, all other terms to the right
-28w=20
w=20/-28
w=-5/7

See similar equations:

| x2-3x-8=0 | | 8n-(3n+8)=3 | | |-2x-1|=11 | | .5(2x-3)^2=11 | | −5+7g=3g+9 | | 5g-6=1-g | | 1/4(17x-8)=-1/5(21-12x) | | 5g-10+4=1-g | | -2b-4b=24 | | 2.5x-3/4(2x+5)=3/8 | | 1.43x=8 | | 7(p+1)=9-9 | | 2.5x-3/4(2x+5)=38 | | -9=-7x+4x | | 6(n+4)=-2 | | 9n^2-2n-10=0 | | 20000=1.15x+14 | | 2n+15=39 | | 5x-5/6x-5=4/5 | | 21/5x-3/4(2x+5)=3/8 | | 7=p-6 | | w–7-4= -3 | | 11x-2=9x-4 | | 2/3x-7=4x-19 | | 14z=-6.8+4.20 | | 17=3(g=3)-g | | 4(x+12)=-4(-12+11x)* | | 5/y+2=3/y | | -12(x-4)=6(4x-10)* | | Y=1/3*(12x-15) | | x2=25676 | | -4k+295k-6)=-3k-39 |

Equations solver categories